Design of Green Hybrid Cementitious Composite for Sustainability Enhancement - Awang, Hanizam; Richard, Alonge Olayiwola; Arminda, Wenny (International Journal of Sustainable Construction Engineering and Technology, 2020)
Built environment sustainability is progressively coming to the upfront in the design of infrastructure as well as in the process of decision making for maintenance work. In confronting this, there is a need for the development of innovative green cement-based materials. These materials should be invented based on the needs of the final application in which they will be implemented. The actions of ignoring the connection between the developments of material, design of structures and sustainability objectives which can result to expensive, short life span, and resource-intensive structures that will need a higher cost of maintenance in a short while are becoming obsolete. This study presents the development of a design framework which was used to produce green hybrid cementitious composites for infrastructure implementation. By means of intentional and careful control of composites constituents and the tailoring of the materials similar to engineer cementitious composites, cement-based hybrid cementitious composites were developed and the mechanical properties are presented. Metakaolin, (MK) and nano-silica (nSi) in colloid form, as well as epoxy, were used as partial replacement of cement content at 12%. Fibers, oil palm, coconuts and artificial barchip were used at 2%. The impact of all these hybrid materials was tested at certain ages of 7, 28 and 90 days. The result shows that despite the replacement, the hybrid cementitious composites performed better in terms of mechanical properties than the same control sample without Metakaolin, nano-silica and epoxy.